Aid after enrollment: Impacts of a statewide grant program at public two-year colleges. (December 2018) - Anderson, Drew M.; Goldrick-Rab, Sara
Highlights: Financial aid can buffer against unexpected changes after college enrollment. We study a randomly assigned supplement to the Pell Grant at two-year colleges. We do not detect substantial increases in college attainment from the added grants. Recent research points to complexity as a barrier which is as important as cost. This aid added complexity for some which may have reduced effectiveness on average. Abstract: Most students who begin at community colleges do not finish with a degree. The net price of college commonly shifts after enrollment, and there is little evidence on how these shifts affect two-year degree completion. This study provides evidence on the impacts of a private program that offered supplemental grant aid to students with demonstrated financial need, who were already enrolled at public two-year colleges in Wisconsin. An evaluation using a randomized control group and data from over 4, 000 students in multiple cohorts, fails to confirm substantial increases in persistence or degree completion caused by the grant program. We highlight some features of implementation that added complexity and may have reduced the effectiveness of the grant program.